2018
DOI: 10.1007/s00404-018-4867-5
|View full text |Cite
|
Sign up to set email alerts
|

Instrument usage in laparoscopic gynecologic surgery: a prospective clinical trial

Abstract: We analyzed the current instrument usage in laparoscopic gynecological surgeries. The results of our standardized investigation suggest ways to reduce the time required for surgery and provide starting points for the standardization of the work routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The work by Stotz et al [ 1 ] describes the type and usage of instruments and trocars during a median of 103 gynaecological laparoscopic interventions. This data can be used to estimate leakage during a hypothetical intervention to add perspective to the individual measurement results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Stotz et al [ 1 ] describes the type and usage of instruments and trocars during a median of 103 gynaecological laparoscopic interventions. This data can be used to estimate leakage during a hypothetical intervention to add perspective to the individual measurement results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, a perfect gas seal is difficult to achieve, with minor leaks of CO 2 through the incision, the trocars and the surgical instruments. In certain procedures with higher pressures, longer operating times, or frequent instrument changes this can result in the leakage of several hundred litres of gas into the operating theatre [ 1 ].…”
mentioning
confidence: 99%
“…Early stage studies have shown prominent attention given to gas leakage through the trocar (port) [2,35]. And no data currently exists in literature that attempts to quantify gas leakage during instrument use and exchange, despite the fact the literature shows that such events are overly abundant in every laparoscopic procedure [36][37][38]. More work is needed to better understand the level of risk of clinician safety in today's OR to guide us to a safer OR of the future around this rising issue, brought to the forefront of people's minds during this global COVID-19 pandemic.…”
Section: Need For More Research To Accurately Quantify the Problemmentioning
confidence: 99%
“…The Instrument Full Insertion/Removal scenario was used to simulate an instrument exchange or other such removal and/or insertion event, which is commonly experienced during laparoscopy for each and every case. For example, scope removals are often performed to clean the lens, and instruments are commonly removed to achieve access through a different port or to exchange them out for a new instrument [36,37,[40][41][42][43]. Each instrument-port configuration also helped to represent a few different levels of such combinations seen in today's OR.…”
Section: Test Procedures For Each Use Case Scenariomentioning
confidence: 99%
“…Gynecological laparoscopic surgery has been progressively and successfully introduced into practice as, this minimally invasive surgery is associated with low morbidity, less postoperative pain, and improved cosmetics [4]. In addition to diagnostic indications, operative procedures at the time of laparoscopy proved to enhance both spontaneous and assisted conception rates [5].…”
Section: Introductionmentioning
confidence: 99%